(untitled) (International relations and international law Journal, 2018)
This article analyzes cooperation between Kazakhstan and France in the area of culture, education and science. Interest of Kazakhstan in France is quite broad and substantiated. Cultural cooperation between Kazakhstan and France is one of the priority areas and is an important aspect of bilateral cooperation. France, as a leading European power, in virtually all areas of creativity is the capital of the art world, has become the main cultural landmark for majority of countries. This article discusses and comprehensively analyzes the main events of cultural exchange between Kazakhstan and France, the interstate dialogue in the field of science and education. It is considered cooperation in literature, cinema, music, dance, theater by means of an exchange of actors and participation in performances, cinema festivals, book exhibitions, symposiums and other similar activity. And also in the article it is shown that, cooperation between France and Kazakhstan in the area the higher education is under construction at three levels: European, bilateral and institutional level. Key words: Kazakhstan, France, culture, education, science.